Recent fieldguides to neotropical stingless bees - Gonzalez, Victor H. (Journal of Melittology, 2014)
Book review of:Oliveira, F.F., de, B.T.T. Richers, J.R. da Silva, R.C. Farias, & T.A. de Lima Matos. 2013. Guia Ilustrado das Abelhas “Sem-Ferrão” das Reservas Amanã e Mamirauá, Amazonas, Brasil (Hymenoptera, Apidae, Meliponini). IDSM [Instituto de Desenvolvimento Sustentável Mamirauá]; Tefé, Brazil; 267 pp.  ISBN 978-85-88758-27-8 [paperback].Giraldo, C., A. Rodríguez, F.J. Chamorro, D. Obregón, P. Montoya, N. Ramírez, V. Solarte, & G. Nates-Parra. 2011. Guía Ilustrada de Polen y Plantas Nativas Visitadas por Abejas: Cundinamarca, Boyacá, Santander, Sucre, Atlántico y Sierra Nevada de Santa Marta, Colombia. Unibiblos, Universidad Nacional de Colombia; Bogotá, Colombia; 230 pp.  ISBN 978-95-87199-83-3 [spiral bound].